A MAMOA 5 DO LEANDRO (MAIA, NORTE DE PORTUGAL). RESULTADOS INTERDISCIPLINARES PARA OS ESTUDOS DOS RITOS FUNERÁRIOS NEOLÍTICOS - Oliveira, César (2021)
The megalithic monument known as Mamoa 5 do Leandro is located in the parishes of Nogueira and Silva Escura, in the municipality of Maia. The monument, part of a necropolis, was found partially destroyed, mainly in the chamber area, still preserving a head orthostat with remains of a painted motif composed by a red and black sun-shaped central ‘solar’ symbol between two straight vertical segments. Several publications are focused on the monument´s typology and on the uncovered materials, but little information is known on the pigments composition and on the paintings techniques, and an interdisciplinary approach was followed to their study, including chromatography, X-ray diffraction and scanning electron microscopy with electron-beam microanalysis. The analytical results showed a red pigment, prepared with iron oxide minerals, associated with vegetable oils as organic additives, and a black pigment, corresponding to charcoal without any organic additives or binders. The solar motif was first drawn with charcoal and then painted red. A comparison of this monument with others in Galicia suggests that it was built and decorated in the first half of the 4th millennium BC.